Model Pembelajaran Kooperatif Tipe Picture And Picture Dalam Berbicara Bahasa Jerman - Sunarti Sunarti; Wahyu Kurniati Asri; Syamsu Rijal (Phonologie : Journal of Language and Literature, 2021)
Abstract. This study aims to determine the planning, process, and results of the Picture and Picture cooperative learning model in the German speaking skills of XI grade students of SMA Negeri 9 Bulukumba. This research is a classroom action research which consists of two cycles. The subjects of this study were students of class XI IBB SMA Negeri 9 Bulukumba, totaling 27 students. This research data consists of two types, namely qualitative data and quantitative data. Qualitative data was obtained through observation, while quantitative data was obtained through speaking skills tests in cycle I and cycle II. The data were analyzed using the percentage technique. The results showed that the students' speaking skills in the first cycle reached 69.25% and increased to 89.03% in the second cycle. These results indicate that the application of the Picture and Picture type cooperative learning model in the German speaking skills of class XI IBB students of SMA Negeri 9 Bulukumba increases.